THE STUDY OF ARABIC CONSTELLATION FROM THE BOOK SUWAR AL-KAWAKIB AL-THABITA USING STELLARIUM SOFTWARE - Putraga, Hariyadi; Butar-Butar, Arwin Juli Rakhmadi; Hidayat, Muhammad; Firdaus, Muhammad Dimas (Universitas Islam Negeri Alauddin Makassar, 2022)
The constellations originating from Arab civilization were still very little known and studied. Al-Ṣūfi's book, al-Kawākib al-Thābitah, contains the record of coordinates, approximate magnitudes, and star details with graphs. This study examines the difference of stars in the sample constellation, compares the visual appearance of the illustrations on the Stellarium software, and studies the differences between the western constellations and the Arabic constellations. The result shows some differences between the constellations of the almagest and al-Kawākib al-Thābitah in the number of stars in the sample constellations, differences in illustrations from the orientalized figures, and the star magnitude in al-Ṣūfi's work that similar to Ptolemy's works. Al-Sufi identified a total of 134 additional stars, 65 stars located in the Northern constellations, 41 stars in the Zodiac constellation, and 28 stars in the Southern constellations. His observations showed that the magnitude values of 520 stars out of a total of 1022 stars were identical between al-Sufi and Ptolemy. Stellarium provides an excellent visual presentation of the Arabic constellations according to Al-Sufi's book that shows position, illustration, and mapping in the night sky.